“Antagonismo in vitro de trichoderma spp. Y bacillus subtilis frente al patógeno lasiodiplodia theobromae en mora”. - Masaquiza Jiménez, John Jairo (2024)
In Ecuador, blackberry cultivation suffers considerable losses due to a disease known as "descending death," affecting approximately 65% of production. This pathology causes significant annual losses and reduces crop yield. This study was conducted to explore the potential of Trichoderma spp. and Bacillus subtilis as sustainable alternatives for biological control. The research was carried out in the Microbiology Laboratory of the Technical University of Cotopaxi, Salache campus. Strains of Lasiodiplodia theobromae, isolated from blackberries accession OQ879511, were obtained in collaboration with the University San Francisco de Quito (USFQ). Monosporic crops of the pathogen were prepared for microscopic analysis and dual crops assays. The bio control agents used were Trichoderma spp., obtained from the laboratory collection at UTC, and a commercial strain of Bacillus subtilis. Counts were made in a Neubauer chamber to obtain suspensions at two concentrations: 10^8 and 10^4. 50 μl of each concentration were added, and a line of 3.5 cm was drawn at the end of the Petri dish, on PDA medium, using a test tube. For Trichoderma spp., pures discs of 8 mm diameter of each fungus were cultivated, which were then seeded at the ends of the Petri dish with PDA medium at a distance of 3.5 cm. The fungus inhibition results of Lasiodiplodia theobromae in each of the confrontations were analyzed using the INFOSTAT program. After obtaining significant results in the analysis of variance, the Tukey test at 5% was performed to determine different levels of significance. The results indicated that treatment T1 (Trichoderma spp. against Lasiodiplodia theobromae) showed the best result, with an inhibition of 2.94 cm. This result demonstrates the ability of this treatment to reduce both the incidence and severity of the disease when directly confronting to the phytopathogen under in vitro conditions.